Perkembangan Konstitusi di Indonesia Melalui Peran Mahkamah Konstitusi dalam Penegakan Hukum Konstitusi di Kaji Menurut Undang-Undang Nomor 24 Tahun 2003 Tentang Mahkamah Konstitusi - Fakhrian Yudiansyah; Eneng Rika; Laela Sari; Tegar Wahyu Hidayat; Yeli Yana (Lembaga Pengembangan Kinerja Dosen, 2024)
The Constitution is the fundamental foundation for the establishment and development of an independent state, reflecting the framework of a democratic and just political life. As an integral part of the constitutional system, the Constitutional Court (MK) plays a crucial role in safeguarding justice and democracy through its oversight and constitutional interpretation functions. The Constitutional Court in Indonesia functions as a guardian of the constitution, ensuring that all components of the state and society consistently implement the constitution. Indonesia's constitutional history shows significant dynamics of change, with the 1945 Constitution undergoing various amendments before finally being reaffirmed in the reform era. The establishment of the Constitutional Court in 2003 reflected the spirit of reform to guarantee human rights and the rights of citizens that had previously been neglected. With a special task in handling constitutional cases, the Constitutional Court aims to maintain government stability and overcome the problem of multiple interpretations of the constitution that occurred in the past.